Promene seruma MMP-9, NSE, MPO nivoa i prognostičnih faktora uticaja kod pacijenata sa intrakranijalnom aneurijom koji su podvrgnuti interventnoj emboliziji u različitom tajmingu lečenja: Prognostic factors in aneurysm embolization - Wu, Chunmiao; Dong, Xingyu; Li, Qiang; Liu, Shengming; He, Yuhao; Zhang, Yang; Zhang, Sunfu (Journal of Medical Biochemistry, 2023)
Background: To analyzse the changes in serum levels of matrix metalloproteinase-9 (MMP-9), neuroenolase (NSE), myeloperoxidase (MPO) and prognostic factors in patients with intracranial aneurysm (IA) undergoing interventional embolization at different treatment times. Methods: A retrospective analysis was made of 200 IA patients admitted to our department from January 2018 to June 2021 was performed. All patients underwent interventional embolization. According to the timing of surgery, the patients were divided into an early group (n=120, onset to surgery ≤72 h) and a delayed group (n=80, onset to surgery >72 h). The effect of embolization, complications and neurological deficit scale (NDS) scores were compared between the two groups. Serum MMP-9, NSE and MPO levels were compared before and after surgery, and the prognosis of all patients within 2 years after surgery was assessed by the Glasgow outcome scale (GOS) and divided accordingly into the good prognosis group (n=147) and the poor prognosis group (n=53) accordingly, and the prognostic factors influencing the patients were analysed univariately and multifactorially. Results: After surgery, the rate of complete embolismwas higher in the early group than in the delayed group (P<0.05). After surgery, there was no statistical significance in the comparison of the individual complication rates in both groups (P>0.05). At 3d, 1 month, and 6 months after surgery, the NDS scores of patients in both groups were lower than those before surgery, and the within-group comparison of the NDS scores of patients in both groups at different time points was statistically significant (P<0.05). After surgery, serum MMP-9, NSE, and MPO levels were lower in both groups than before surgery, and they were lower in the early group than in the delayed group (P<0.05). GOS results showed that within 2 years after surgery, there were 97 and 23 cases with good and poor prognosis in the early group and 54 and 26 cases with good and poor prognosis in the delayed group, respectively, and the good prognosis rate in the early group was higher than that in the delayed group (P<0.05). Multifactorial analysis showed that delayed surgery, aneurysm in the posterior circulation, aneurysm neck width >4.5 mm, Fisher grade III-IV, Hunt-Hess grade III-IV, and hypertension were all independent risk factors for poor prognosis after IA interventional embolization (P<0.05). Conclusion: Early interventional embolization in IA patients can improve their complete embolization rate and reduce serum MMP-9, NSE, and MPO levels; delayed surgery, aneurysm in the posterior circulation, aneurysm neck width >4.5 mm, Fisher grade III-IV, Hunt-Hess grade III-IV, and hypertension are strongly associated with poor prognosis after interventional embolization in IA patients.